Zero‐Reflectance Metafilms for Optimal Plasmonic Sensing. Issue 2 (23rd November 2015) - Huang, Fumin; Drakeley, Stacey; Millyard, Matthew G.; Murphy, Antony; White, Richard; Spigone, Elisabetta; Kivioja, Jani; Baumberg, Jeremy J.
Abstract : An ultrathin layer of metasurface that almost completely annihilates the reflection of light (>99.5%) over a wide range of incident angles (>80°) is experimentally demonstrated. Such zero‐reflectance metafilms exhibit optimal performance for plasmonic sensing, since their sensitivity to changes of local refractive index is far superior to films of nonzero reflectance. Since both main detection mechanisms tracking intensity changes and wavelength shifts are improved, zero‐reflectance metafilms are optimal for localized surface plasmon resonance molecular sensing. Such nanostructures have significant opportunities in many areas, including enhanced light harvesting as well as in developing high‐performance molecular sensors for a wide range of chemical and biomedical applications. Abstract : Zero‐reflectance metafilms are demonstrated to be optimal plasmonic sensors. Complete annihilation of the reflectance ( R ) of a highly reflective surface such as Si can be achieved with an ultrathin layer of Au nanoparticles. Such zero‐reflectance metafilms show much superior plasmonic sensing performance than those of nonzero reflectance films.